Motherhood and Anesthesiology: A Survey of the American Society of Anesthesiologists. Issue 4 (December 2020) - Kraus, M.B.; Dexter, F.; Patel, P.V.; Dodd, S.E.; Thomson, H.M.; Girardo, M.E.; Hertzberg, L.B.; Pearson, A.C.S.
Abstract : ( Anesth Analg . 2020;130:1296–1302) Over the last 2 decades, rates of women entering medical school have risen to near parity with men. However, despite gender equivalence in medical school enrollment, rates of female anesthesiologists lag severely behind. Though data are lacking in anesthesiology, causes of the leadership and specialty gaps for surgical residencies have been reviewed in recent publications, finding potential deterrents such as changing career plans due to motherhood, lack of formally institutionalized maternity leave policies, gender discrimination, perceived stigma associated with pregnancy, and perceived incompatibility of surgery with rewarding family life. In congruence with these findings for surgery, a study of major medical specialties determined anesthesiology to have the highest rate of maternal discrimination. The aim of this study was to survey women members of the American Society of Anesthesiologists (ASA) to better understand motherhood-related factors associated with women's likelihood to recommend against a career in anesthesiology.